2019
DOI: 10.1098/rsos.181089
|View full text |Cite
|
Sign up to set email alerts
|

How real are observed trends in small correlated datasets?

Abstract: The eye may perceive a significant trend in plotted time-series data, but if the model errors of nearby data points are correlated, the trend may be an illusion. We examine generalized least-squares (GLS) estimation, finding that error correlation may be underestimated in highly correlated small datasets by conventional techniques. This risks indicating a significant trend when there is none. A new correlation estimate based on the Durbin–Watson statistic is developed, leading to an improved estimate of autore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…It was suspected that the statistical significance attributed to some of the parameters in this new model by the t-statistic may have been inflated, so we investigated taking spatial correlation into account, by using generalised least squares (GLS) regression instead of OLS regression [33]. This analysis confirmed that parameter dN 1ERAI , nominally the same parameter as dN 1 but from a more recent and much more extensive ECMWF reanalysis [34], was not significant after all.…”
mentioning
confidence: 81%
See 3 more Smart Citations
“…It was suspected that the statistical significance attributed to some of the parameters in this new model by the t-statistic may have been inflated, so we investigated taking spatial correlation into account, by using generalised least squares (GLS) regression instead of OLS regression [33]. This analysis confirmed that parameter dN 1ERAI , nominally the same parameter as dN 1 but from a more recent and much more extensive ECMWF reanalysis [34], was not significant after all.…”
mentioning
confidence: 81%
“…In the case of the N sA0.1 parameter, the mean difference is -0.14 N-units, but an unweighted mean is an OLS estimate, which ignores spatial correlation that may exist between nearby stations. This correlation may be taken into account with a GLS estimate, using the methods described in [33], or later in this paper, as the mean difference is a regression model with only an intercept and no other parameters. In the case of N sA0.1 , the GLS estimate of the difference over 20 years is −0.40 N-units, but this is only marginally significant, with a 95% confidence interval from −0.84 to +0.04 Nunits.…”
Section: Potential Impact Of Climate Changementioning
confidence: 99%
See 2 more Smart Citations
“…The order in which the TMS variables were added was based on the Pearson’s correlation results; TMS variables with strongest correlation with the dependent variable (MS symptoms severity) were added first. Independence of observations was tested with Durbin-Watson test (~2.0) [ 104 ] and strength of the relationship was evaluated using R 2 [ 105 ]. The size of the coefficient of determination (regression R 2 ) was interpreted as ‘very weak’ < 0.3, ‘weak’ 0.3–0.49, ‘moderate’ 0.5–0.69, and ‘strong’ > 0.7 [ 106 ].…”
Section: Methodsmentioning
confidence: 99%